Effects of color mixing components on offset ink and printing process - AYDEMİR, CEM; ARMAN KANDIRMAZ, EMİNE; YENİDOĞAN, SEMİHA (TAYLOR & FRANCIS INC, 2017)
In printing, the most important element is to obtain the correct substrate and ink combination. Transparent white and opaque white are used for the lightening of printing inks, but they are also an important component for the mixing of inks. The primary objective of this study was to assess the result of using transparent and opaque white in mineral oil-based offset printing inks on the rheological and printability properties of these inks as well as the ideal mixing ratios in terms of print quality. Transparent and opaque white were added into the standard offset magenta ink variable ratios. Differences in ink viscosity, tack, and flow (rheological) values affect such parameters as adhesion, transferability, and printing stability in these inks. Prints were made on matt-coated papers of the same grammage with these inks, and contact angle, solid ink density, color strength, and print gloss values of these ink films were measured. Color differences (Delta E*(ab)) of inks in comparison to the standard ink were calculated and the effects of transparent and opaque white on the rheological and printability properties of the ink were presented. Finally, the ideal mixture ratios of transparent and opaque white into the ink were determined in terms of print quality and recommendations were presented.
Keywords: Color; ink; lightening; mixing; offset; opaque; printability; transparent